Survival Outcomes of Patients Treated with Hypofractionated Stereotactic Body Radiation Therapy for Parotid Gland Tumors: a Retrospective Analysis - Karam, Sana D.; Snider, James W.; Wang, Hongkun; Wooster, Margaux; Lominska, Christopher; Deeken, John F.; Newkirk, Kenneth; Davidson, Bruce; Harter, K.William (Frontiers in Oncology, 2012)
Background: To review a single-institution experience with the management of parotid malignancies treated by fractionated stereotactic body radiosurgery (SBRT) Findings: Between 2003 and 2011, 13 patients diagnosed with parotid malignancies were treated with adjuvant or definitive SBRT to a median dose of 33 Gy (range 25–40 Gy). There were 11 male and 2 female patients with a median age of 80. Ten (10) patients declined conventional radiation treatment and 3 patients had received prior unrelated radiation therapy to neighboring structures with unavailable radiation records. Six (6) patients were treated with definitive intent while 7 patients were treated adjuvantly for adverse surgical or pathologic features. Five (5) patients had clinical or pathologic evidence of lymph node disease. Conclusions: At a median follow-up of 14 months only 1 patient failed locally, and 4 failed distantly. The actuarial 2-year overall survival, progression free survival, and local-regional control rates were 46%, 84%, and 47%, respectively. Statistical analysis revealed surgery as a positive predictor of overall survival while presence of gross disease was a negatively correlated factor (p<0.05).